ELISA and LC-MS/MS Method for Detecting 19-Nortestosterone Residue in Animal Tissues - Jiang, J.Q.; Yang, X.F.; Fan, G.Y.; Wu, S.X.; Huang, H.G.; Liu, X.Y.; Wang, Z.L.; Yang, L.; Zhao, X.N. (Asian Journal of Chemistry, 2011)
Two different analytical methods for the detection of 19-nortestosterone (NT) residue in bovine have been developed and the comparison was also performed. For this purpose, EDC method was employed to synthesize the artificial antigen of NT-17-BSA. The results of IR and UVvisible spectra indicated that the artificial antigen was synthesized successfully and the conjugation ratio was 18:1. Based on the checkerboard titration results, an icELISA standard curve was established. The linear range was from 0.04 to 86 ng/mL, with LOD and IC50 value of 0.02 ng/mL and 1.2 ng/mL, respectively. For LC-MS/MS analysis, analytes were separated using a mobile phase solution of 1 % formic acid in water/acetonitrile/methanol (60:20:20, v/v/v) at a flow rate of 0.2 mL/min. The ultraviolet detector was operated at 242 nm and the injection volume was 10 μL. Positive chemical ionization mode was used and the relative collision energy was optimized to 28 %. When applied in spiked bovine samples, the correlation coefficients (R2) of the icELISA and LC-MS/MS data were 0.9963 in muscle, 0.9988 in liver and 0.9984 in kidney, respectively. The results suggest that it was an advantage through coupling of icELISA as screening method and LC-MS/MS as confirmatory method for detecting 19-nortestosterone residues in animal edible tissues.